The Effect of Damage to Irrigation Assets on The Management of The Irrigation Network in The Weliman Irrigation Area, Malaka Regency-NTT - Donny Harisuseno; Tri Budi Prayogo; Andryanus Bere (Fakultas Teknik, Universitas Brawijaya, 2023)
Malaka Regency as an agricultural area does not yet have good irrigation asset maintenance management as a supporter of success in the agricultural sector. The obstacle faced in dealing with damage to irrigation assets is the difficulty in determining maintenance priorities due to the government's limited budget. It causes maintenance activities to be carried out in the stage. This study aimed to assess the physical condition of assets, asset functioning, service areas, maintenance costs, and maintenance priorities. The handling solution is carried out by developing a strategy for developing the Weliman irrigation area using a SWOT analysis. In the research results, the irrigation assets prioritized for maintenance are right secondary channel 1, left primary channel 5, distribution structure 3, left primary channel 3, left primary channel 4, distribution structure 4, primary channel left 2, and distribution structure 2. The results of the SWOT analysis, the recommended strategy is the Growth strategy, namely, maximizing the strengths owned to take advantage of existing opportunities.